2019
DOI: 10.1109/access.2019.2916600
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis and Enhancement of an Image Encryption Scheme Based on Bit-Plane Extraction and Multiple Chaotic Maps

Abstract: Recently, an image encryption scheme combining bit-plane extraction with multiple chaotic maps (IESBC) was proposed. The scheme extracts binary bit planes from the plain-image and performs bitlevel permutation and confusion, which are controlled by a pseudo-random sequence and a random image generated by the Logistic map, respectively. As the rows and columns of the four MSBPs are permuted with the same pseudo-random sequence and the encryption process does not involve the statistical characteristics of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The network realizes image contrast enhancement by learning some mapping relationships between the input images and the noise maps. Considering the weak representation ability of a shallow network, it is necessary to increase the network depth [38]- [43]. However, as the network depth increases, the difficulty of network training will increase, as well.…”
Section: A Establishment Of the Neural Networkmentioning
confidence: 99%
“…The network realizes image contrast enhancement by learning some mapping relationships between the input images and the noise maps. Considering the weak representation ability of a shallow network, it is necessary to increase the network depth [38]- [43]. However, as the network depth increases, the difficulty of network training will increase, as well.…”
Section: A Establishment Of the Neural Networkmentioning
confidence: 99%
“…In the same way, Li et al [ 19 ] broke Pak’s work [ 12 ] by comparing the differences between several pairs of chosen plain-cipher images. After analyzing the image cryptosystem [ 9 ], Liu et al [ 20 ] reported that the correlation information among adjacent plain pixels cannot be erased by the row/column-wise permutation, thereby leaving an open door for the known-plaintext attack. Wen and Yu [ 21 ] ascertained that, in the image cryptosystem [ 9 ], keys are not associated with the plain images.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a large number of image cryptosystems based on chaotic systems have been found to be unsafe [24,25,26,27,28,29,30,31]. These cryptosystems cannot resist chosen/known plaintext attacks [32,33,34,35,36,37,38,39,40,41] because they possess plaintext-unrelated equivalent keys. A chosen plaintext attack method in [32] cracked the scheme in [24] with only 18 attacks for 256Ă—256-sized images.…”
Section: Introductionmentioning
confidence: 99%
“…They also presented a chosen plaintext attack method to decode the scheme in [25] with MN+1 pairs of chosen plaintext and cipher-text images, where M and N are the height and width of the image, respectively. In [34], Liu et al proposed an effective known plaintext attack method and an effective chosen plaintext attack method to crack the scheme in [26], and suggested some improvement measures. Wen et al in [36] successfully cracked the image encryption scheme in [27] with the help of a chosen plaintext attack and a chosen cipher-text attack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation